The Effectiveness of Online Single Submission in Improving The Productivity of Civil Servants in The Investment and One-Stop Integrated Services Agency of Padang City West Sumatra Province - Tumija Tumija; Yani Alfian; Muhammad Akmal Sabri (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2025)
This study examines the effectiveness of the Online Single Submission (OSS) system in improving civil servant productivity at Padang City DPMPTSP. Using a descriptive qualitative approach with interviews, participatory observation, and documentation, the study applies Subagyo's theory of effectiveness, covering target accuracy, dissemination, objectives, and program monitoring. Results show that of eight sub-indicators across four dimensions, only civil servant ethics and monitoring performed well, while competence development, ease of implementation, facilities and infrastructure, media, civil servant knowledge, and evaluation were unsatisfactory. The study concludes that OSS implementation remains ineffective and recommends enhancing human resource capacity through training, optimizing information technology use, improving infrastructure, and strengthening coordination to achieve better service outcomes.